The role of attention for insight problem solving: effects of mindless and mindful incubation periods - Rummel, Jan; Iwan, Franziska; Steindorf, Lena; Danek, Amory H. (Journal of cognitive psychology, 2021)
Incubation periods may be beneficial for insight problem solving either because they allow to mentally disengage from incorrect solution attempts or because they provide additional opportunities to rethink a problem. We investigated whether incubation periods either filled with an easy stimulus-response task, which does not require much attention, a more difficult stimulus-response task, or a mindfulness intervention, which should both require higher sustained-attention levels, differently affect problem solving. Results showed no difference in solution rates and frequencies of Aha! Experiences between the stimulus-response-task groups, which generally thought more, and the mindfulness group, which generally thought less about yet unsolved problems during the incubation period. Results did not change when individual differences in working-memory capacity and trait mind-wandering were controlled for. These findings suggest that short incubation periods may not be overly beneficial for insight problem solving, independent of whether they allow to periodically redirect attention to pending problems or not.
Online veröffentlicht: 4. November 2020
Gesehen am 15.05.2024